HemisFair '68: Texas World's Fair - Pearl Pavilion (Plastichrome of Texas, Inc.)
Pearl Brewing Company's Pavilion, with its indoor and outdoor dining, refreshment and entertainment areas, evokes the charming mood and easy living of turn-of-the-century San Antonio.